Comparison of absorption and excretion of test compounds in sucking versus chewing pests. - Clara I Römer; Roman Ashauer; Beate I Escher; Juliane Hollender; René Burkhard; Kristin Höfer; Michel Muehlebach; Anke Buchholz (PLoS ONE)
A critical understanding of how pests interact with active ingredients is essential for the development of new insect control solutions to maintain crop quality and quantity by reducing insect damage. Absorption of insecticides into insect bodies of targeted pest species is the first critical step that confounds the efficacy of insecticides. This study investigated how different feeding behaviour of two pests, Myzus persicae and Spodoptera littoralis, affects the absorption, metabolism, and excretion (AME) of seven insecticidally inactive test compounds. A feeding contact assay for the chewing pest (Lepidopteran larvae) and an oral ingestion assay for the sucking pest (aphids) was used to investigate the AME of test compounds with agrochemical-like structural motifs. The standardized assays comprised of an exposure period with treated diet and a subsequent depuration period with untreated diet. The results showed that S. littoralis larvae differed from M. persicae in their compound quantities absorbed into the insect body and in their excretion products at the end of the exposure or depuration periods. We suggest that this is caused by their different ingestion types and rates resulting in different absorption and excretion quantities. Further, we found differences in the metabolism (timing and biotransformation pathways) of compounds between both species. Notably, certain compounds remained detectable in both pests after the depuration period, suggesting compound and species-specific metabolism and excretion. Our results highlight the complex interplay between feeding biology of insects, in particular the critical role of excretion products, and the exposure to different compounds that lead to species-specific AME.